Metarhizium robertsii with insecticidal activity for the control of the fruit fly (Anastrepha obliqua), the main pest in mango crop in Colombia - Lozano Tovar, María Denis; Ballestas Álvarez, Karen Lorena; Sandoval Lozano, Luis Andrés; Palma Mendez, Gloria Milena; Barrera Cubillos, Gloria Patricia (Research Square, 2024)
The aim of this study was to evaluate and select entomopathogenic fungi that produces insecticidal compounds for the control of adults of Anastrepha obliqua Macquart (Diptera: tephritidae), that are the main pest of mango (Mangifera indica L. Bark) in Colombia. One strain of the species Metarhizium robertsii with insecticidal activity was selected. By column fractionation, an active fraction was obtained, this compound caused mortalities higher than 90% after 48 hours of exposure. By HPLC it was determined that the active fraction is composed of more than 22 metabolites. Identification of the extracts by UHPLC MS/MS reveal the presence of destruxin in the groups E, D, A and B (destruxin E-diol, destruxin D, destruxin D1, destruxin D2, destruxin A2, destruxin A, destruxin A3, dihydrodestruxin A, desmB, destruxin B2, destruxin B, and destruxin B1). The evaluation of the insecticidal capacity of the organic fractions obtained by HPLC indicated that the extract obtained from the isolate Metarhizium robertsii had a compound with high activity on adults of A. obliqua (destruxin A) causing massive mortality of up to 100%, 48 hours after treatment administration. Furthermore, two other compounds with medium activity were found (destruxin A2 and destruxin B), showing mortalities between 60.0 and 81.3% respectively. The extract of the isolate MT008 of M. robertsii showed higher insecticidal activity and is a potential source for the control of A. obliqua.